LEVEL OF ANXIETY OF PREGNANT MOTHER IN FACING SECTIO CAESAREA OPERATIONS IN DKT SIDOARJO HOSPITAL - Marlita Dewi Lestari; Kusuma Wijaya Ridi Putra; Dimyati Dimyati (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2019)
Background: Mothers who undergo labor with sectio caesarea can experience anxiety because they have never experienced surgery or do not know about the actions to be taken.Objective: The study aimed to determine the maternal anxiety level of preoperative sectio caesarea in the Maternity Room of the DKT Hospital in Sidoarjo.Method: The research design used was descriptive method with cross sectional approach. The population in this study were patients who will undergo labor with sectio caesarea in the Maternity Room of the DKT Hospital in Sidoarjo. Sampling technique with accidental sampling. The instrument used was the Hamilton Rating Scale for Anxiety (HRS-A) which was adopted from the book Stress, Anxiety, and Depression Management (Hawari, 2004), which included 14 psychological symptoms of anxiety.Results: The results showed that the most anxiety level of preoperative sectio caesarean mothers was moderate anxiety as many as 25 people (50%).Conclusion: The anxiety level of mothers who will undergo Caesarean section surgery is moderate anxiety, so special care is needed by health workers. Handling that can be given in the form of health education about surgical procedures and post-surgical treatment. In addition, providing knowledge to the family so that they will continue to motivate mothers who will face the caesarean section surgery. Keywords: Level of anxiety, caesarean section surgery, labor.